Harwood-Nuss' clinical practice of emergency medicine - Wolfson, Allan B.; Cloutier, Robert L.; Hendey, Gregory W.; Ling, Louis, 1954-; Rosen, Carlo L.; Schaider, Jeffrey; Cole, Jon B. (Wolters Kluwer, 2021)
"This seventh edition of Harwood--Nuss' Clinical Practice of Emergency Medicine continues in the tradition of its predecessors as an authoritative, up-to-date, and concise single-volume resource that encompasses essentially all areas of emergency medicine"--